بیسویں صدی کے مکالمات بین المذاہب کا مختصر تاریخی و تنقیدی جائزہ۔Contemporary Inter-Fath Dialogues : A Critical Analysis from Historical Angle - ڈاکٹر نور حیات خان; ڈاکٹر محمد ریاض خان (الإيضاح, 2013)
Dialogue is a medium of human understanding. Through dialogue one can express himself clearly.In the modern times human civilization is globally facing so many challenges.In this situation inter-faith dialogue can bring peace in the world. Because it is dialogue which help men understand each other and bring them close to each other. But in the contemporary period inter-faith dialogues bave almost failed to achieve the noble targers. This article seeks to disclose why inter-faith dialogues have so far proved meaningless.